2018
DOI: 10.1126/sciadv.aap9416
|View full text |Cite
|
Sign up to set email alerts
|

Attosecond-resolution Hong-Ou-Mandel interferometry

Abstract: A new Hong-Ou-Mandel interferometer protocol achieves few-attosecond (nanometer) photon path delay resolution.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
173
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(179 citation statements)
references
References 29 publications
4
173
1
1
Order By: Relevance
“…This approach provides photon path delay measurements with a precision of the order of a micrometre. However, recent work [35] has shown that this precision can be greatly increased by fixing the interferometer delay close to the point of maximum steepness of the HOM interference dip, indicated by a vertical dashed line in Fig. 3(b).…”
mentioning
confidence: 99%
“…This approach provides photon path delay measurements with a precision of the order of a micrometre. However, recent work [35] has shown that this precision can be greatly increased by fixing the interferometer delay close to the point of maximum steepness of the HOM interference dip, indicated by a vertical dashed line in Fig. 3(b).…”
mentioning
confidence: 99%
“…While this value has been chosen to guarantee that the mean square error is a valid approximation, the analysis of prior information carried out in[5] demonstrates that, in fact, this choice allows us to approach the Cramér-Rao bound using the type of probes considered here. Note that the fact that some states and measurements require a certain amount of prior knowledge to be useful due to the multi-peak structure of their likelihood is ubiquitous in phase-estimation problems[5,25,49], although it can be overcome using adaptive techniques[25].…”
mentioning
confidence: 99%
“…The HOM effect can be used to measure optical delays between different paths, as was already noted in the seminal 1987 paper by Hong, Ou, and Mandel. This feature lies at the heart of what has now become known as HOM interferometry and was recently used in a series of HOM‐based time delay sensors with a wide dynamic range and novel protocols such as quantum optical coherence tomography (QOCT) …”
Section: Entanglement‐based Quantum Imagingmentioning
confidence: 99%